ATMOSPHERE MONITORING SYSTEM FOR PRACTICAL TRAINING OF STUDENTS PURSUING DEGREES IN ENVIRONMENTAL SCIENCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Issues related to preservation of the environment are among the most important global problems in the beginning of 21st century. These are central for the planet as a whole and also for each individual country, region and city. Solutions for said problems are discussed on various levels: legislative, judicial, economic and technical. Formation of professional ecological education is an essential task nowadays. In our teaching activities with students in the master’s program “Ecology and Environment Preservation” at University of Mining and Geology „St. Ivan Rilski“ we strive to ensure the necessary theoretical and practical competences of the future specialists – ecologists. In this paper, we present some major topics of the Atmosphere & Environment Course, as well as the system of practical training of students for field measurements.